Analisis Karakterisitik Permainan Bulutangkis Tunggal Putra dan Tunggal Putri - Supriyanto, Nugroho Agung; Rasyid, Ainur (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2018)
Badminton has some types of stroke, including offensive and defensive stroke in match. The purpose of this study was to know the characteristics of badminton game in male single and female single based on types of stroke that score points. The method used in the study was descriptive method with percentage techniques. All types of stroke scoring points were recorded. The result showed that the highest points produced by unforced errors opponent. The conclusion of this study was the player who commited less unforced errors had a great chance to win the match.  AbstractBadminton has some types of stroke, including offensive and defensive stroke in match. The purpose of this study was to know the characteristics of badminton game in male single and female single based on types of stroke that score points. The method used in the study was descriptive method with percentage techniques. All types of stroke scoring points were recorded. The result showed that the highest points produced by unforced errors opponent. The conclusion of this study was the player who commited less unforced errors had a great chance to win the match.